2011
DOI: 10.1016/j.iccn.2011.01.001
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of patients and their families of visiting whilst in an intensive care unit – A hermeneutic interview study

Abstract: SummaryAim: The aim of this study was to interpret and understand the meanings of the lived experiences of visiting of patients in an ICU and their families. Method: The research design was hermeneutic, based on interviews. This study includes 12 interviews with seven patients and five relatives who had been in an ICU. The interview text was interpreted in a Gadamerian manner as different plays with actors and plots. Findings: Patients' narratives could be divided into two parts; recall of real life and unreal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 34 publications
(45 reference statements)
1
26
0
1
Order By: Relevance
“…1,2 Dissatisfaction with this traditional visitation paradigm has pushed families to become more involved in their loved one's care with a greater focus on the transparency of health-care quality. [3][4][5][6][7][8][9][10][11] This focus is evidenced by calls to action for hospitals to examine their current intensive care unit (ICU) visitation practices [12][13][14][15][16][17][18][19] and to try entirely open, nonrestrictive ICU visiting, labeling any visiting restrictions as a relic, unnecessary, and potentially harmful to the patient's safety. 13,14 and emotional support to their loved one (Table 1).…”
Section: Design Focus Groupsmentioning
confidence: 99%
“…1,2 Dissatisfaction with this traditional visitation paradigm has pushed families to become more involved in their loved one's care with a greater focus on the transparency of health-care quality. [3][4][5][6][7][8][9][10][11] This focus is evidenced by calls to action for hospitals to examine their current intensive care unit (ICU) visitation practices [12][13][14][15][16][17][18][19] and to try entirely open, nonrestrictive ICU visiting, labeling any visiting restrictions as a relic, unnecessary, and potentially harmful to the patient's safety. 13,14 and emotional support to their loved one (Table 1).…”
Section: Design Focus Groupsmentioning
confidence: 99%
“…, McKiernan & McCarthy , Cypress , Eriksson et al . ), the needs of relatives in the ICU environment (Verhaeghe et al . , El‐Masri & Fox‐Wasylyshyn , Blanchard & Alavi , Al‐Mutair et al .…”
Section: Introductionmentioning
confidence: 99%
“…Hupcey (2000) has described the overarching need of ICU patients to feel safe and this feeling of safety is influenced by family and nurses on the ICU. For this reason, the perspectives of both patients and their families are important during the time on the ICU (Eriksson et al, 2011) and the presence of family members is reported to be important in the support of the critically ill patient (Bergbom and Askwall, 2000;Hupcey, 2001;Engström and Söderberg, 2004;McKiernan and McCarthy, 2010). Family-centred care has been highlighted in recent decades and families are being offered a more active role in the care in the ICU.…”
Section: Introductionmentioning
confidence: 99%